Pengembangan Media Pembelajaran Bahasa Arab Menggunakan Aplikasi GBA (Gemar Berbahasa Arab) Kelas VIII MTSN 6 Hulu Sungai Utara (April & October, 2025)
The GBA (Gemar Berbahasa Arab) application is an Arabic language learning media developed for eighth-grade students at MTsN 6 Hulu Sungai Utara. Designed as an M-Learning platform, it allows students to study Arabic anytime and anywhere without requiring internet access. Although not yet available on the Play Store, the app is distributed via WhatsApp. The content is adapted from textbook material, then developed into a digital format to enhance learning.This study aims to provide an alternative Arabic learning tool during online learning periods, introduce students to mobile-based learning experiences, and contribute to Arabic language education. Using a Research and Development (R&D) method, the researcher conducted interviews, digitized learning material, developed and edited the app, and validated it with three experts in media, content, and design. The application was then tested by ten student representatives. Results show that the GBA app is feasible and effective, with positive expert validation and student responses. The study also outlines the app development process, validation results, and student feedback. Overall, the GBA app offers a creative and engaging approach to Arabic learning and encourages educators to innovate by integrating technology into language education.